Elevated serum ferritin level as a predictor of reduced survival in patients with sporadic amyotrophic lateral sclerosis in China: a retrospective study. Issue 3 (3rd April 2019) - Sun, Qionghua; Yang, Fei; Wang, Hongfen; Cui, Fang; Li, Yanran; Li, Siyuan; Ren, Yuting; Lan, Wenjie; Li, Mao; Zhu, Wenjia; Sun, Xiaosun; He, Zhengqing; et al.
Abstract: Objective: The objective of this study was to compare iron metabolic variables in the serum and cerebrospinal fluid (CSF) of patients with sporadic amyotrophic lateral sclerosis (sALS) with those of patients with multiple system atrophy (MSA) and control subjects. We also assessed the correlations of these variables with sALS progression and severity and estimated their roles in predicting prognosis. Methods: We retrospectively collected iron metabolic parameters, including serum levels of iron, ferritin, transferrin levels and total iron binding capacity and the CSF level of ferritin, from 435 sALS patients, 176 MSA patients and 431 control subjects. Results: Serum ferritin levels were significantly higher in the sALS group compared with the MSA and control groups in both males ( p = 0.001 and p < 0.0001, respectively) and females ( p = 0.034 and p < 0.0001, respectively). However, serum transferrin levels were significantly lower in females of the sALS group compared with the MSA ( p = 0.016) and control ( p = 0.015) groups. The CSF ferritin level and the serum levels of total iron binding capacity and iron were similar among the sALS, MSA and control groups. Survival analysis demonstrated that higher serum ferritin levels were predictors of reduced survival of sALS patients. No correlations between iron metabolic variables and clinical parameters were found. Conclusion: An elevated serum ferritin level is associated with reduced survival of sALS patients. However, the levels of iron metabolic parameters were not associated with clinical deterioration or disease severity at diagnosis.